The Prewar Business Cycle Reconsidered: New Estimates of Gross National Product, 1869-1908 - Romer, Christina D. (Journal of Political Economy, 1989)
This paper shows that the existing estimates of prewar gross national product exaggerate the size of cyclical fluctuations. The source of the exaggeration is that the original Kuznets estimates are based on the assumption that GNP moves one-for-one with commodity output valued at producer prices. New estimates of GNP for 1869-1918 are derived using the estimated aggregate relationship between GNP and commodity output for the interwar and postwar eras. The new estimates of GNP indicate that the business cycle is only slightly more severe in the pre-Worid War I era than in the post-World War II era.